Globalization and the competitiveness of regional blocks in comparative perspective - Bernhard Fischer (Hamburg Institute of International Economics (HWWA), 1998)
Given the uncertain outcome for regional trade arrangements and given the need for improved international competitiveness due to ongoing globalization it seems advisable to promote at a national level those policies which might help to enhance both integration into the regional and world markets. Prominent candidates for such policies are the build-up of infrastructure at the national and regional level and human capital formation (Fischer, Gleich, Grabendorff 1994). According to estimates by the World Bank (1994) about 60 billion US would have to be invested in infrastructure up to the year 2000 to enable Latin America the successful continuation of its exports led growth strategy. Presumably the greatest competition between nations, in terms of bidding for a larger share of mobile resources, occurs in the context for the managerial and technological skills of successful multinational enterprises, including the competition for the talent of highly skilled professionals - academic researchers, engineers and other professionals (Hufbauer, Stephenson 1995 and Garelli 1996). Therefore human capital development should be a priority on the policy agenda. Finally, the enforcement of institutional competition could be a deliberate strategy in improving the competitiveness of economies (North 1995). Institutions are the constraints that human beings impose on human interaction including formal rules, informal constraints and enforcement characteristics. Given the importance of FDI as a driving force of both regional and global integration there is an urgent need to ensure a fair international competitive environment, in particular with regard to foreign direct investment. Investment issues are currently the subject of discussion or negotiation in a number of regional fora. One important initiative was the launching, in May 1995, of negotiations aimed at the conclusion of a Multilateral Agreement on Investment among the Members of the OECD. The main aim of these negotiations is to eliminate discrimination between foreign and domestic investors. The agreement is intended to provide a broad framework for international investment, with high standards for the liberalization of investment regimes and the protection of investment, and with effective dispute management. Other regional and international fora have already addressed investment issues, or are in the process of doing so, including APEC, ASEAN, SADC, NAFTA and MERCOSUR, as well as initiatives pursued in the context of the Free Trade Area. Other proposals aim at the negotiations of multilateral rules on FDI in the framework of international organizations with global membership. In particular, the WTO has been mentioned as an appropriate forum for such negotiations as the inter-twining of investment and trade requires a more integrated approach to international rule-working. The WTO already deals with certain aspects of investment issues in the context of the agreements on trade in services, trade-related investment measures and trade-related aspects of intellectual property rights. In perhaps one of its most important decisions, the WTO Singapore Conference in December, 1996, set up a working group to examine competition policies. Yet the big question is whether trade liberalisation and WTO discipline will be best served by adding to the trading system a global codex, harmonizing national competition policies ex ante, or by mutually recognizing wellfunctioning national competition policies. While sound economic arguments support the latter, prevailing country-of-destination principles conjure up concerns that the former will dictate the approach (Spinanger 1997). The further development of regional and international rules on FDI needs to consider at least the following key issues (UN 1996): − Investment measures that affect entry and operations of foreign investors. Particularly relevant are issues relating to admission and establishment, ownership and control, operations, incentives and investment-related measures; − Application of certain standards of treatment. Particularly relevant are issues of national treatment, most-favoured-national treatment, and fair and equitable treatment; − Measures dealing with broader concerns, including the proper functioning of the market. Particularly relevant are issues related to restrictive business practices, transfer pricing, transfer of technology, employment, the environment, and illicit payments; − Investment protection and the settlement of disputes. Particularly relevant are issues relating to expropriations and property taking in general, abrogation of state contracts with investors, transfer of funds, and dispute settlements.
Keywords: 330; Handelsregionalisierung; Internationaler Wettbewerb; Standortwettbewerb; Globalisierung; Welt; EU-Staaten; MERCOSUR-Staaten; NAFTA-Staaten; ASEAN-Staaten